Character Development of Students Through Islamic Education Extracurricular Activities at Perbaungan High School - Priantono, Djody; Ritonga, Asnil Aidah (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
This study examines the character development of students through Islamic Education extracurricular activities at SMAN 1 Perbaungan. The focus of this research is on the efforts made in implementing Islamic Education extracurricular activities at SMAN 1 Perbaungan to foster students' behavior. This qualitative research employs a phenomenological approach. The findings indicate that the school's efforts in nurturing students' character at SMAN 1 Perbaungan are carried out through various activities, including giving students the opportunity to deliver short speeches to their peers during activities, weekly worship sessions/Tazkir Fridays, Quran reading programs, and other activities. These extracurricular activities aim to instill and enhance religious beliefs and values among students.